Forecasting the occurrence of injection-induced heterogeneous slip on rock fractures - Fang, Zhou (2023)
Forecasting the slip behavior of a non-uniformly pressurized, heterogeneous creeping rock fracture, either aseismic creep or dynamic slip, is challenging based solely on laboratory and field measurements. Here we reported a simple, robust method to determine whether an aseismic creep is maintained or transitions to a dynamic slip during fluid injection. We reproduced the non-uniformly distributed fluid pressure and the resulting heterogenous aseismic creep on a critically stressed fracture and revealed the ratio of shear stress and frictional resistance corresponding to the fluid pressure front reaching or exceeding unity at the occurrence of dynamic slip. The determination of frictional resistance is based on the Mohr-Coulomb failure criterion with fluid pressure and friction coefficient on discrete segments of the fracture, and the length of fluid pressure front is calculated from hydraulic diffusivity and elapsed time. We used the experimental results of 9 shale fractures and 3 granite fractures to verify this method. We can also observe how the fluid pressure front propagates until the ratio of shear stress and frictional resistance approaches unity or is constrained with the ratio far below unity. This method has the potential for rapidly forecasting the injection-induced slip on a low-permeability rock fracture and simply characterizing the slip behavior of a natural, large-scale fracture during fluid injection.